Shape readout of AT‐rich DNA by carbohydrates. Issue 7 (July 2014) - Kumar, Sunil; Newby Spano, Meredith; Arya, Dev P.
ABSTRACT Gene expression can be altered by small molecules that target DNA; sequence as well as shape selectivities are both extremely important for DNA recognition by intercalating and groove‐binding ligands. We have characterized a carbohydrate scaffold (1) exhibiting DNA "shape readout" properties. Thermodynamic studies with 1 and model duplex DNAs demonstrate the molecule's high affinity and selectivity towards B* form (continuous AT‐rich) DNA. Isothermal titration calorimetry (ITC), circular dichroism (CD) titration, ultraviolet (UV) thermal denaturation, and Differential Scanning Calorimetry were used to characterize the binding of 1 with a B* form AT‐rich DNA duplex d[5′‐G2A6T6C2‐3′]. The binding constant was determined using ITC at various temperatures, salt concentrations, and pH. ITC titrations were fit using a two‐binding site model. The first binding event was shown to have a 1:1 binding stoichiometry and was predominantly entropy‐driven with a binding constant of approximately 108 M−1. ITC‐derived binding enthalpies were used to obtain the binding‐induced change in heat capacity (ΔCp) of −225 ± 19 cal/mol·K. The ionic strength dependence of the binding constant indicated a significant electrolytic contribution in ligand:DNA binding, with approximately four to five ion pairs involved in binding. Ligand 1 displayed a significantly higher affinity towards AT‐tract DNA over sequences containing GC inserts, and binding experiments revealed the order of binding affinity for 1 with DNA duplexes: contiguous B* form AT‐rich DNA (d[5′‐G2A6T6C2‐3′]) >B form alternate AT‐rich DNA (d[5′‐G2(AT)6C2‐3′]) > A form GC‐rich DNA (d[5′‐A2G6C6T2‐3′]), demonstrating the preference of ligand 1 for B* form DNA. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 720–732, 2014.